การออกแบบและสร้างเครื่องกำเนิดกระแสอิมพัลส์ฟ้าผ่าซ้ำ - อานันทร์ หยงสตาร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This thesis reports design and construction of a multiple lightning current impulse generator that can produce a sequence of up to four lightning current impulses. This generator can vary the lightning parameters such as time interval between successive impulses and peak magnitude of impulses. The current impulse is generated by storing energy in capacitors, which is charged to a required voltage and discharged through a series R-L circuit into the test object. Information is provided for the controlling of triggering unit by using microcontroller MCS-51 system and the recording of impulses by using a Digital Storage Oscilloscope. The test results showed that the generator can generate multiple lightning current impulse which has a standard impulse waveform of 8 /2 0 µs. The maximum amplitude of impulses current are 5 kA .